Low temperature heat treatments of AA5754-Ti6Al4V dissimilar laser welds: Microstructure evolution and mechanical properties. (1st March 2018) - Leo, P.; D'Ostuni, S.; Casalino, G.
Graphical abstract: Highlights: Low temperature heat treatments lead to microstructural evolution in 5754-Ti6Al4V laser welds. The microstructural evolutions change with heat treatment temperature and laser heat input. Due to the heat treatment, the Al3 Ti compound grew at the Al-Ti weld interface. The growth of the intermetallic layer and particles decreases the joint tensile performances. The hardness of 5754/Ti6Al4V alloy slightly decreases/increases with heat treatment. Abstract: This paper presents the effects of the post welding heat treatments (PWHT) performed at 350 °C and 450 °C on the microstructure evolution and mechanical properties of AA5754 and Ti6Al4V dissimilar laser welds. The microstructure and tensile properties of the welds before and after low temperature treatment were analyzed. The off-set welding technique was applied to limit the formation of brittle intermetallic compounds during the welding process. The laser beam was directed onto the titanium side at a small distance from the aluminum edge. The keyhole formed and the full penetration was reached in the titanium side of the weld. Thereafter, the aluminum side melted as the heat that formed the keyhole transferred from the titanium fused zone. Two different energy lines (32 J/mm and 76 J/mm) were used. In this manner, a fused and a heat affected zones was revealed on both sides of the weld. Several intermetallic compounds formed in the intermetallic layer between the two metals. The thickness and the composition of the intermetallic layer depended on the welding parameters and the post welding heat treatment. The hardness and tensile properties of the welds before and after the post welding heat treatment were measured and analyzed.